3-Hydroxyacyl CoA Dehydratase 2 Is Essential for Embryonic Development and Hepatic Metabolic Function Under a Low-Fat, High-Carbohydrate Diet - Lengyun Wei; Fengli Wang; Luoxue Hua; Qun Wang; Benfei Hu; Ziye Yang; Letao Li; Chenfeng Liu; Kezhen Wang (Biology, 2025)
The conversion of carbohydrates into fatty acids is central for energy storage and the development and functioning of organs. Our previous study revealed that Hacd2 deficiency alleviates the fatty liver and diabetes induced by HFD. This study aimed to explore the roles of Hacd2 in organ development and metabolic homeostasis under an LFHCD, which still need to be more deeply explored. We found that the germline deletion of Hacd2 impairs long-chain fatty acid synthesis, which caused embryonic abnormalities after 7.5 days and led to embryonic lethality, as confirmed via photograph and hematoxylin-eosin staining. We next constructed Hacd2LKO mice and found that Hacd2LKO mice were largely normal when fed a chow diet, except for reduced inguinal white adipose tissue formation and glucose metabolism. Meanwhile, under an LFHCD, Hacd2 deletion markedly controlled body weight and white adipose tissue formation, leading to lower cholesterol and triglycerides in serum; however, it unexpectedly resulted in enlarged liver volume, hepatocyte swelling and nuclear abnormalities, and infiltration of inflammatory cells, including macrophages, neutrophils and dendritic cells. Furthermore, inhibition of Hacd2 also reduced triglyceride levels and the expression of related lipogenic genes during adipocyte differentiation, as confirmed via RNA interference analysis. These findings highlight the critical roles of Hacd2 in embryonic development and metabolic diseases, revealing its protective function in maintaining liver homeostasis under an LFHCD. Therefore, targeted interventions involving Hacd2 for metabolic diseases must take into account dietary changes and the functioning of the liver.